2015
DOI: 10.3390/ijerph120201577
|View full text |Cite
|
Sign up to set email alerts
|

Contamination and Spatial Variation of Heavy Metals in the Soil-Rice System in Nanxun County, Southeastern China

Abstract: There is an increasing concern about heavy metal contamination in farmland in China and worldwide. In order to reveal the spatial features of heavy metals in the soil-rice system, soil and rice samples were collected from Nanxun, Southeastern China. Compared with the guideline values, elevated concentrations of heavy metals in soils were observed, while heavy metals in rice still remained at a safe level. Heavy metals in soils and rice had moderate to strong spatial dependence (nugget/sill ratios: 13.2% to 49.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 31 publications
(46 reference statements)
6
56
1
Order By: Relevance
“…According to Paya-Perez et al, 19 inherent interferences of some elements such as Zn were attributable to CV values greater than 100% in a comparative ICP-MS and ICP-OES study on soil pollution in Abardeen, UK. Zhao et al 28 suggested that soil's complex nature could be the reason for CV values of beyond 100% for Ni and Cr in Chinese soil-rice systems using atomic spectroscopy. In both analytical techniques, CV values of Ti and Fe were the lowest, whereas values of Co, Zn, Ni, and Sr were relatively the same, which could infer to the ability of the 2 techniques to quantify these elements precisely.…”
Section: Discussionmentioning
confidence: 99%
“…According to Paya-Perez et al, 19 inherent interferences of some elements such as Zn were attributable to CV values greater than 100% in a comparative ICP-MS and ICP-OES study on soil pollution in Abardeen, UK. Zhao et al 28 suggested that soil's complex nature could be the reason for CV values of beyond 100% for Ni and Cr in Chinese soil-rice systems using atomic spectroscopy. In both analytical techniques, CV values of Ti and Fe were the lowest, whereas values of Co, Zn, Ni, and Sr were relatively the same, which could infer to the ability of the 2 techniques to quantify these elements precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, one can at best estimate Ω[Z(x) ≥ Z c ]. In fact, it is necessary to do this in such a way that the estimate at any place x 0 approximates the conditional probability, given the data, that Z(x) equals or exceeds Z c (Liu et al, 2006;Zhao et al, 2015).…”
Section: Geostatistical Analysismentioning
confidence: 98%
“…Soil pollution by heavy metals is a significant environmental problem worldwide. In particular, heavy metal pollution of surface soils due to intense industrialization and urbanization has become a serious concern in many developing countries [16][17][18]. Multi-elemental analysis of sediment may reveal the presence of heavy metals which are contaminants and may have toxic influence on ground water and surface water and also on plants, animals and humans [19].…”
Section: Introductionmentioning
confidence: 99%